The multiple intelligence theory for the teaching of languages - María Encarnación Carrillo García; Amando López López (Universidad de La Rioja, 2014)
In the following essay we analyse the Multiple Intelligence Theory of Howard Gardner focus on the teaching of languages, in order to describe its main points, such us: its description; the types of intelligences explained in it; and the activities, that some authors describe, for developing this theory in the teaching and learning language context.